An indicator species highlights continuous deadwood supply is a key ecological attribute of boreal old‐growth forests. Issue 5 (16th May 2021) - Martin, Maxence; Tremblay, Junior A.; Ibarzabal, Jacques; Morin, Hubert
Abstract: Old‐growth forests are optimal habitats for many woodpeckers, which are often themselves excellent indicators of deadwood‐associated biodiversity. Old‐growth forests are, however, heterogeneous ecosystems in terms of structure, composition, and deadwood characteristics, thus implying a varied use of these forests by woodpeckers. In boreal landscapes, old‐growth stands are threatened by forest harvesting; however, there is little information in regard to the consequences for biodiversity with the loss of specific types of old‐growth forests. This study aimed to assess how the black‐backed woodpecker ( Picoides arcticus ), a biodiversity indicator species associated with old‐growth forest attributes, uses different types of old‐growth forests for its foraging needs. We identified woodpecker foraging marks in 24 boreal old‐growth forest stands in eastern Canada that were dominated by black spruce ( Picea mariana ), located within the home range of eight black‐backed woodpeckers. We identified the various old‐growth forest types using a typology based on the structural attributes of old‐growth stands. We classified the sampled stands into four old‐growth forest types, corresponding to different successional stages (recent or old, relative to the onset of the old‐growth stage), composition (pure black spruce or mixed black spruce–balsam fir [ Abies balsamea ]), and productivity (ongoing paludification or not). The black‐backed woodpecker foraged in all types of old‐growth forests, but favored dense old‐growth forests that were not paludified and that showed a high temporal continuity (i.e., old‐growth dynamics probably started more than a century ago). The temporal continuity of the old‐growth state allows for the continuous supply of large, slightly decayed snags, the preferred foraging substrates of the black‐backed woodpecker. The old‐growth forest type most favored by this woodpecker is, however, also the forest type most often targeted first by logging operations. Protecting the biodiversity associated with recent deadwood in managed areas thus requires maintaining a sufficient area and density of dense, old‐growth black spruce‐dominated forests in managed areas.